Surgical management of carotid body tumor – Is Shamblin classification sufficient to predict surgical outcome?. (April 2017) - Law, Y; Chan, YC; Cheng, SW
Background: The study aims to conduct a review of the surgical management of carotid body tumor. Methods: Consecutive patients with CBT who received surgical interventions from January 1994 to January 2014 at our institution were reviewed. Clinical, operative, pathological and follow up information were reported. Results: Twenty patients (four males; median age was 36) with 21 CBT operations were recorded during the period. One patient undertook sequential operations for bilateral CBTs. Patients had 19 neck mass, 1 incidental finding and 1 facial nerve palsy. Six CBTs (28.6%) were Shamblin class I, ten (47.6%) were class II and five (23.8%) were class III. Nine CBTs had preoperative conjunctive embolization. Two operations required internal carotid artery resection and reconstruction. Four patients received subtotal resections, while 17 achieved complete resection. Complications included two major strokes, three hoarse voice and two Horner's syndrome. Shamblin class was significant predictor of operative time, blood loss, and whether complete resection accomplished, but could not predict postoperative complication. With median follow up period of 94 months, there was no tumor recurrence found in those had complete resection. Conclusions: This small cohort showed that Shamblin class was significant in predicting technical difficulties but could not predict occurrence of complications.